FARMERS’ PERCEPTIONS OF SOIL EROSION AND MANAGEMENT STRATEGIES IN SOUTH BENGAL IN INDIA - KUMAR SHIT, Pravat; SANKAR BHUNIA, Gouri; MAITI, Ramkrishna (European Journal of Geography, 2023)
Soil erosion is an imperative environmental deterioration that leads to serious impact on physical, economical and ecological in developing countries. Present study investigates farmers’ views of soil erosion problems and their conservation knowledge and practices in the Kangsaboti watershed (South Bengal, India) to understand the complex inter-relationships between perception of farmers’ knowledge and soil water conservation (SWC). Data was obtained from a survey of 540 farm households and informal discussions selected by stratified random sampling from upper, middle and lower catchment at Paschim Medinipur, Bankura and Purulia districts respectively. The analysis reveals that farmer age, farming experience, farm training, education and numbers of economically active household members are positively responsible to soil erosion and SWC in the study area. Consequently, potential knowledge of farmers is to be harnessed effectively to mitigate the problem through perception of benefits from conservation of natural resources.